Analysis of the Implementation of Contractor Safety Management System (Csms) on the Readiness to Implement Yantek Vendor Work After Natural Disasters - Dimas Dewantoro; Adithya Sudiarno (Jurnal Impresi Indonesia, 2026)
This study aims to analyze the effect of implementing the Contractor Safety Management System (CSMS) on the readiness of Yantek vendors to carry out their work after natural disasters. The research background is based on the high occupational safety risks in post-disaster conditions, which require the readiness of integrated work safety systems, behaviors, and controls. This study employs a quantitative approach through a survey of 88 respondents consisting of Yantek vendor management and workers, project supervisors, K3L personnel, and CSMS auditors. Data analysis was conducted using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method with the assistance of SmartPLS software. The results showed that CSMS and safety behavior have a positive and significant effect on the readiness to carry out vendor work. Furthermore, K3 culture, the availability of work equipment, risk management, and supervisory patterns were found to significantly mediate the effect of CSMS on post-disaster work readiness. These findings confirm that the successful implementation of post-disaster work is highly dependent on the effectiveness of CSMS implementation, supported by safety behaviors and comprehensive K3 support systems.